Chemical study of some species related to the Malvaceae family that growing in the Al-Diwaniya Governorate - Ali Kadhim AL-Aridhee , Hussein; Hussein Baji Al-Lami , Suhaila; Ayad Jassim, Safa (Al-Qadisiyah Journal of Pure Science, 2019)
The present study dealt with the chemical content of the leaves extract of six species from Malvaceae family in AL-Diwaniyah governorate, where all species are present in it. Its: Hibiscus sabdariffa (L.), Abelmoschus esculentus (L.), Moench Althaea ludwigii (L.), Malva parviflora (L.) and Gossypium hirsutum (L.). Chemical compounds were identified using the GC-MASS gas chromatography technique. The results showed that these species contained several secondary metabolites, which included phenols, turbines, alkaloids, kanates, esters and steroids. The presence of some compounds involved more than one species, which helped isolate the species from each other, such as the 2-Pentenal compound, 5-phenyl, found in the extract of the leaves Ab. esculentus and Al. ludwigii and the compound Benzene, 1,2,1 - (1,2-cyclobutanediyl) bis-, cis- which was found in all species under study except M. parviflora. It was observed through the study that the two genus Hibiscus contained the most common compounds by six compounds supported their return to the same genus, as for compound Styrene was presence in all species. The species were also distinguished by other compounds such as 10-Undecyn-1-ol and Z-4-Dodecenol, which were found in Al. ludwigii and H. rosa-sinensis, which enhanced the taxonomic importance of this study.